On the Formation of the Secondary Art Market in the 18th-Century Paris - Agratina Elena E. (Художественная культура)
In the 18th-century France the secondary art market was rapidly developing. The key figures in that process were marchands, or art dealers. The article is aimed at investigating different aspects of marchands’ activity. Not only did they do their business, but they also had an influence on the entire cultural environment of the time. The author of the article refers to foreign, especially French, sources and research literature. The article is relevant due to the lack of studies of the topic under consideration in the Russian language. The works by foreign scholars are numerous but they have hardly been translated into Russian and thus are almost inaccessible to the Russian audience. Moreover, the author aims to present her personal perspective on the issues of art trade. The text of the article is divided into three parts each of them focusing on a particular phenomenon. The first part reveals the activity of Parisian marchands: how it started, where the majority of their shops were situated and why, where they travelled and what for, who they dealt with and what their concern was. The second part highlights the formation of auction practices which became widespread in the second part of the 18th century and contributed to the establishment of the genre of fine art catalogue. The third part portrays marchands as experts, advisers of wealthy collectors, and creators of many art collections. Linking artistic and social processes, this research will be useful for the development of such a field in art studies as the social history of art.